Marine Carotenoids and Cardiovascular Risk Markers - Riccioni, Graziano (Molecular Diversity Preservation International, 2011)
Marine carotenoids are important bioactive compounds with physiological activities related to prevention of degenerative diseases found principally in plants, with potential antioxidant biological properties deriving from their chemical structure and interaction with biological membranes. They are substances with very special and remarkable properties that no other groups of substances possess and that form the basis of their many, varied functions and actions in all kinds of living organisms. The potential beneficial effects of marine carotenoids have been studied particularly in astaxanthin and fucoxanthin as they are the major marine carotenoids. Both these two carotenoids show strong antioxidant activity attributed to quenching singlet oxygen and scavenging free radicals. The potential role of these carotenoids as dietary anti-oxidants has been suggested to be one of the main mechanisms for their preventive effects against cancer and inflammatory diseases. The aim of this short review is to examine the published studies concerning the use of the two marine carotenoids, astaxanthin and fucoxanthin, in the prevention of cardiovascular diseases.